Labour Market Imbalances in Canada, 1966-1983 - Betcherman, Gordon (Relations industrielles / Industrial Relations, 1986)
This paper considers two questions. First, what imbalance trends have characterized the Canadian labour market since 1966? And, second, what factors explain these trends.